Calculation of critical core configurations of a research reactor using MTR, IRT-4M, VVR-KN fuel assemblies - Tran, Quoc Duong; Nguyen, Nhi Dien; Huynh, Ton Nghiem; Nguyen, Kien Cuong; Nguyen, Minh Tuan (Nuclear Science and Technology, 2018)
This paper presents calculation results to determine critical core configurations and a minimum number of fuel assemblies (FAs) or uranium mass of a research reactor loaded with three types of FAs such as MTR, IRT-4M and VVR-KN. The MCNP5 code and ENDF/B7.1 library were applied to estimate characteristics parameters of the fuel types and the whole core. Infinitive multiplication factor kinf, neutron flux distribution and neutron spectra of the fuels were calculated. The reactor core configurations with three fuel types were modeled in 3-dimensions, and then the effective multiplication factors keff, relative radial power distribution of each configuration were also evaluated. From calculation results, twelve fuel loading schemes were chosen based on lowest uranium mass or smallest number of FAs loaded into the core. In addition, two full core configurations using VVR-KN and MTR FAs and consisting of beryllium reflectors, vertical irradiation facilities, horizontal neutron beam ports, etc. have been proposed for further consideration in thermal hydraulic calculations and safety analysis.